TINJAUAN VIKTIMOLOGI PADA ANAK KORBAN PROSTITUSI (STUDI KASUS “X” DI PEKANBARU) - Riky Novarizal (SISI LAIN REALITA, 2019)
Child prostitution is an act of obtaining or offering a child's sexual services by a person or to another person in return for money or other remuneration. Trafficking of children for sexual purposes or prostitution is a violation of human rights and is one of the worst forms of child exploitation due to its exploitative nature, both in the process of withdrawing children into prostitution and in their work and impacting the physical, mental and moral development of children, because exploited children are vulnerable to physical, psychological, sexual abuse. Through qualitative research methods by conducting in-depth interviews it can be concluded that, the tendency of perpetrators to choose girls as victims is due to the vulnerability of girls caused by age, physical condition, weak mental condition. The victim's vulnerability makes them more accessible to the perpetrator. The perpetrators can approach the victim in various places ranging from the public space, with various methods, such as lure prize money. The child as a prostitute victim also plays a role in the prostitution of this child, because the crime committed is actually used by the victim or child to get a big advantage and the cooperation between the victim is the child and the perpetrator is pimps due to the provocation or encouragement of the child so that the pimp acting and taking the role of prostitution in children.